Pengaruh Literasi Keuangan, Kualitas SDM, dan Kemudahan Akses Pembiayaan Mikro Syariah Terhadap Perkembangan UMKM di BMT Beringharjo KCP Dolopo - Syahru Rofah Febrianti; Ajeng Pipit Fitriani (Niqosiya: Journal of Economics and Business Research, 2024)
Low levels of financial literacy can be an obstacle to business development. Human resource quality problems such as lack of skills, low productivity, or inability to adapt to market changes. Lack of access to microfinance can hinder business expansion and business diversification. The aim of this research is to determine and test the influence of financial literacy, quality of human resources, and ease of access to sharia microfinance on the development of MSMEs. This research uses quantitative methods, data collection using a questionnaire of 100 respondents. The results show that financial literacy has a negative and significant effect on the development of MSMEs, the quality of human resources has a positive and significant effect on the development of MSMEs, and Ease of Access to Sharia Microfinance has a positive and significant effect on the development of MSMEs. The results of the F Test show that the three independent variables have a simultaneous influence on the development of MSMEs.